PENGUATAN KOMUNIKASI KELUARGA DALAM PENCEGAHAN PENYEBARAN COVID-19 - Prahastiwi Utari; Eka Nada Shofa Alkhajar; Tanti Hermawati; Chatarina Heny Dwi Surwati; Firdastin Ruthnia Yudiningrum; Adolfo Eko Setyanto; Annisaa Fitri (Kanigara, 2023)
Family communication is one of the most important forms of communication. Good family communication can prevent the spread of COVID-19. One of the ways is to share information and messages related to the disease. This community service activity was carried out in Karang Village, Delanggu, Klaten. This service activity provides counseling to the target of community service to be able to strengthen and implement good family communication as a means of preventing the spread of COVID-19. The result achieved from this community service activity is that the target of community service realized the importance of strengthening and implementing good family communication to take care of each other in the family from various bad things including COVID-19.